Estimated glucose disposal rate and non-HDL-c/HDL-c ratio with the progression of carotid atherosclerosis: a long-term cohort study - Bingqing Han; Bingqing Han; Jing Ma; Shanshan Liu; Chao Fu; Hao Zhang; Yi Luo; Fei Wang; Qiang Zeng (Frontiers in Medicine, 2025)
BackgroundBoth the estimated glucose disposal rate (eGDR) and the non-HDL-c/HDL-c ratio (NHHR) are associated with cardiovascular disease risk and prognosis. It is unclear whether assessing eGDR and NHHR together improves CAS progression prediction.MethodsThis large cross-sectional and longitudinal cohort study included 7,360 adults who underwent multiple health check-ups at the Chinese PLA General Hospital from October 2009 to December 2023. The relationships of the eGDR and NHHR with CAS progression were determined through multivariable Cox regression analysis and restricted cubic splines (RCS).ResultsDuring a median follow-up period of 30 months, we included 7,360 participants. The restricted cubic spline curve of the correlation between the eGDR and CAS progression was non-linear. There was a positive linear relationship between the NHHR and CAS progression. When the eGDR was <8.71 (median level) mg/kg/min and the NHHR was >2.89, the risk of CAS progression significantly increased. Subgroup analysis revealed that age significantly altered the correlation. The incorporation of the eGDR and NHHR into the basic model significantly enhanced the usefulness of the model for predicting CAS progression. Furthermore, mediation analysis revealed that the NHHR significantly mediated the impact of the eGDR on CAS progression.ConclusionsThis study revealed that a lower eGDR and higher NHHR are associated with an increased risk of CAS progression. The combined assessment of the eGDR and NHHR can enhance the identification of high-risk populations, which is useful for the implementation of active preventive measures.